Sâib-i Tebrîzî dîvânı şerhi - Abū-Bakr Nuṣrat, Ibn-ʿAbdallāh al-Ḫarbūtī,Yakut, Emrullah (Vakıfbank Kültür, 2023)
Sâib-i Tebrîzî; turkish poetry; history and criticism
Keywords: Abū-Bakr Nuṣrat; Ibn-ʿAbdallāh al-Ḫarbūtī; Osmanisch; Ghasel